Case Report: The first account of primary myeloid sarcoma of the testis combined with ipsilateral epididymal epithelioid hemangioendothelioma - Chen, Xi; Liu, Li (Frontiers in Medicine, 2025)
This case report describes a 35-year-old male with primary myeloid sarcoma (MS) of the testis and concurrent ipsilateral epididymal epithelioid hemangioendothelioma (EHE)—an exceptionally rare combination. Myeloid sarcoma typically involves the skin and bone, but testicular involvement is rare, particularly as an isolated tumor without hematologic malignancy. This makes diagnosis challenging. Epithelioid hemangioendothelioma is a rare vascular tumor, typically found in the liver, lungs, and bones, and epididymal EHE is scarcely reported. The patient had a left testicular nodule for 6 months and experienced pain for 2 days. Ultrasound and MRI revealed abnormalities in the left testis and epididymis. Histopathological examination of the epididymal biopsy showed tumor cells with specific morphological features, and immunohistochemistry (IHC) indicated CD31(+), CD34(+), Fli-1(+), ERG(+), Ki-67(+5%+), along with WWTR1-CAMTA1 gene fusion by fluorescence in situ hybridization (FISH), confirming EHE. Subsequently, testicular resection was performed, and the testicular tumor cells were diffusely arranged. Immunohistochemistry (IHC) analysis revealed expression of multiple markers such as CD31, CD34, MPO, LCA, CD99, CD117, and Ki-67(+50%+), leading to the diagnosis of MS. The patient was then treated with the MA chemotherapy regimen. Diagnosing MS requires integration of clinical history, histopathology, and IHC, but misdiagnosis is common due to overlapping features with other malignancies. There is no standard treatment for testicular MS, but early diagnosis is critical. EHE is mainly treated by extensive resection. This case highlights the importance of suspecting MS in differential diagnosis of testicular and epididymal tumors and calls for further research on the potential interaction between MS and EHE in tumorigenesis.